Experimental investigation for influence of sand temperature and sand binder on strength of furan no-bake mould system - Shailee G. ACHARYA; Jeetendra A. VADHER (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2018)
Though the casting process is also known as a process of uncertainty, in the present study, an attempt has been made to investigate the effect of sand temperature, amount of resin and amount of catalyst on compressive strength and scratch hardness of the furan sand mould. The experiments were conducted based on response surface methodology (RSM) and sequential approach using face-centered central composite design. The results show that quadratic model with the removal of some insignificant term is comparatively best fits for compressive strength. Cubic model with the removal of some insignificant term is comparatively best fits for scratch hardness. Sand temperature is dominating contributor to both responses i.e. compressive strength and scratch hardness. Next contributor is an amount of resin followed of an amount of catalyst or hardener.